Pengembangan Modul Berbasis Masalah pada Mata Pelajaran Dasar Listrik dan Elektronika - Albert Putra; Elfizon Elfizon (Jurnal Pendidikan Teknik Elektro, 2020)
Basic Electrical and Electronics Subjects are basic subjects that must be studied by students. In the implementation of learning, there is a lack of handbook modules for students, so that low student motivation has an impact on student learning outcomes. The availability of adequate teaching materials will certainly increase student motivation and make it easier for students to understand the lesson. For this reason, this study aims to produce a valid and practical learning module in Basic Electricity and Electronics (DLE) subjects. The research method used is the Research and Development method with the 4D Model. The research subject was the learning module for class X TKL SMK Negeri 1 Bukittingi in semester 1 of the 2020/2021 academic year. Based on the results of the study, the validity of the learning module from 3 validators (1 media expert lecturer, 1 material expert, and 1 subject teacher) obtained an average of 90% in the valid category. The practicality test with teacher respondents was 90.4% and 23 students obtained an average of 75% stating that the DLE learning module was practical. From the research data above, it can be concluded that the learning module in the DLE subject is valid and practical in the teaching and learning process for Basic Electricity and Electronics